Ethnomethodology: Land and Building Tax (PBB) Collection in Totosan Village - Nosain Norsain; Moh. Faisol (JASa (Jurnal Akuntansi, Audit dan Sistem Informasi Akuntansi), 2023)
The aims of this reseach to find out how the Totosan village government collects PBB P2. Researchers collected research data using observation, interviews, and documentation, which conducted in-depth interviews with 5 informants. Data analysis through the stages of reduction, presentation, conclusion drawing and verification as well as ethnomethodological analysis with the help of NVivo R1 software. The method of PBB P2 collection carried out in Totosan Village is conditional on the value of local wisdom, where tax collection is carried out by (1) visiting the taxpayer directly; (2) provide education about PBB P2; and (3) provide solutions to problems related to P2 PBB collection and provide services in the P2 PBB payment process. In addition, village officials who have this task emphasized that they came to submit SPPT not to collect taxes, so that it seemed as if village officials were officers who collected taxes, even though they were only facilitators who submitted SPPT PBB P2. This study implies the theory that many ways of collecting taxes do not have to rely on existing legal rules because they create fear for taxpayers. Therefore, in ways that are local wisdom as a new alternative in tax collection.